Development of a minimally invasive simultaneous estimation method for quantifying translocator protein binding with [18F]FEPPA positron emission tomography - Praveen Dassanayake; Udunna C. Anazodo; Linshan Liu; Lucas Narciso; Maryssa Iacobelli; Justin Hicks; Pablo Rusjan; Elizabeth Finger; Keith St Lawrence (EJNMMI Research, 2023)
Abstract Background The purpose of this study was to assess the feasibility of using a minimally invasive simultaneous estimation method (SIME) to quantify the binding of the 18-kDa translocator protein tracer [18F]FEPPA. Arterial sampling was avoided by extracting an image-derived input function (IDIF) that was metabolite-corrected using venous blood samples. The possibility of reducing scan duration to 90 min from the recommended 2–3 h was investigated by assuming a uniform non-displaceable distribution volume (V ND) to simplify the SIME fitting. Results SIME was applied to retrospective data from healthy volunteers and was comprised of both high-affinity binders (HABs) and mixed-affinity binders (MABs). Estimates of global V ND and regional total distribution volume (V T) from SIME were not significantly different from values obtained using a two-tissue compartment model (2CTM). Regional V T estimates were greater for HABs compared to MABs for both the 2TCM and SIME, while the SIME estimates had lower inter-subject variability (41 ± 17% reduction). Binding potential (BPND) values calculated from regional V T and brain-wide V ND estimates were also greater for HABs, and reducing the scan time from 120 to 90 min had no significant effect on BPND. The feasibility of using venous metabolite correction was evaluated in a large animal model involving a simultaneous collection of arterial and venous samples. Strong linear correlations were found between venous and arterial measurements of the blood-to-plasma ratio and the remaining [18F]FEPPA fraction. Lastly, estimates of BPND and the specific distribution volume (i.e., V S = V T − V ND) from a separate group of healthy volunteers (90 min scan time, venous-scaled IDIFs) agreed with estimates from the retrospective data for both genotypes. Conclusions The results of this study demonstrate that accurate estimates of regional V T, BPND and V S can be obtained by applying SIME to [18F]FEPPA data. Furthermore, the application of SIME enabled the scan time to be reduced to 90 min, and the approach worked well with IDIFs that were scaled and metabolite-corrected using venous blood samples.